Assessment of training and development and labour turnover in Federal University of Technology, Minna And Ibrahim Badamasi Babangida 2010 -2020 / Sani Yusuf, S. B. Abdulkareem and H. A. Yusuf - Yusuf, Sani; Abdulkareem, S. B.; Yusuf, H. A. (Universiti Teknologi MARA, 2022)
Training and development are assumed to have a very positive effects on workers in every organization most especially universities. They tend to be more productive whenever human capital development are undertaken as policy or strategy as this will eventually lead to productivity. In Nigeria, employee turnover posed serious fundamental challenges in many organization most especially universities. A recent estimate have shown that between 2010 to 2020, more than 4000 teaching staff from various universities leave their various institutions to look for a greener pastures in western countries such as United Kingdom, United States, Canada and Germany. How does training and development affect labour turnover in our universities? The objective of this paper is to determine the effect of training and development on turnover. The hypothesis postulated state that training and development has no significant effect on turnover. Some variables such as training needs, relevance of training and development programmes, proper placement after training, promotion, salary increase, recognition, and career growth were identified to be factors that contribute to labour turnover. The research adopted both secondary and survey research method. The population of the study was 2,010. The sample size was 305. A stratified sample techniques was adopted. The questionnaire were administered, collected and analyzed using descriptive statistical analysis and regression to test the hypothesis. The findings established that these variables has a significant and positive relationship with turnover. The study recommends that workers should be highly motivated with promotion, proper placement, and uninterrupted career growth.